Tatay na si Totoy attitudes of teenage fathers toward parenthood. - Aquino, Mary Christine C.; Booc, Euva Anna M.; Redubla, Christine Marie Alissandra V. (Tacloban City Mary Christine C. Aquino, 2012)
This is a descriptive and exploratory study about the attitudes of teenage fathers toward parenthood. The study was conducted in specific areas of Eastern Visayas, namely Tacloban City, Palo, Dulag, and Dagami, Leyte and Taft, Eastern Samar. The researchers utilized a descriptive research design and conducted interviews with 13 teenage fathers using a 22-item, semi-structured interview guide. In qualifying the attitudes of these teenage fathers, the research was guided by five research problems revolving around the ABC's of attitude. The research questions aim to identify the feelings and emotions of teenage fathers on early parenthood, their roles and responsibilities as parents, how they make sense of their past and present experiences, how they evaluate themselves as parents, and their views and plans for the future. The results showed that teen fathers have the general tendency to evaluate themselves with positive regard. This is because almost all of the teenage fathers responded positively to all the five research questions. It was found that the optimistic attitudes acquired through early parenthood predicted their positive behavior as an individual. These teenage fathers held optimistic values toward their affect, behavior, and cognition, resulting in the teenage father's positive attitudes toward parenthood.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science